# What is #f(x) = int -x^3+x-4 dx# if #f(2) = -3 #?

Use the power rule to integrate.

Combining items (1) and (2), we finish with

By signing up, you agree to our Terms of Service and Privacy Policy

To find ( f(x) = \int_{-x^3}^{x-4} dx ) given that ( f(2) = -3 ), we integrate the function and then use the given value to solve for the constant of integration.

First, integrate the function:

[ f(x) = \int_{-x^3}^{x-4} dx ]

[ f(x) = \left[ x \right]_{-x^3}^{x-4} ]

[ f(x) = (x - (x-4)) - (-x^3) ]

[ f(x) = x - x + 4 + x^3 ]

[ f(x) = 4 + x^3 ]

Now, we use the given information that ( f(2) = -3 ) to solve for the constant of integration:

[ f(2) = 4 + (2)^3 = 4 + 8 = 12 ]

Since ( f(2) = -3 ), we have:

[ -3 = 12 + C ]

Solve for ( C ):

[ C = -3 - 12 = -15 ]

Therefore, ( f(x) = 4 + x^3 - 15 ).

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- How do you integrate #x^2cos4x^3 dx#?
- How do you use partial fraction decomposition to decompose the fraction to integrate #1/((x+2)(x^2+4))#?
- How do you use partial fraction decomposition to decompose the fraction to integrate #4/((x^2+9)(x+1))#?
- Prove that #In=sec^n-2xtanx/n-1+n-2/n-1 In-2#,where #In=∫sec^n dx#. Hence deduce #I4#?
- How do you integrate #int tan^5(2x)sec^2(2x)#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7